Developing a Learning Module 唐诗 (Tangshi) - Mardasari, Octi Rjeky; Muyassaroh, Lukluk Ul; Ventivani, Aiga; Laksana Sakti, Karina Fefi (KnE Social Sciences, 2021)
Poetry is a critical element of literature which must be studied. The language in poetry is a parable language and difficult to understand because the language is rarely used in everyday life. Similarly, classical Chinese poetry preserves ancient Mandarin （文言文） [Wén yán wén] which was used in the past in China. This study is based on the findings of students’ difficulties in understanding the meaning of classical Chinese poetry. The research aimed to develop a learning medium in the form of a famous Chinese classical poetry learning module during the Tang Dynasty. There are three classical Chinese poems in this module, namely, the 静夜思 [ Jìngyè sī] by 李白 [Li Bai]; 春晓 [Chūnxiao] by ̌ 孟浩然 [Meng Haoran]; and 春夜 喜雨 [Chūnyè x ̌iyu] by ̌ 杜甫 [Du Fu], which are accompanied with an explanation of the poetry, learning activities, formative assignments, and evaluation. This study uses the Five Phases of Instructional Design Model developed by Cennamo and Kalk (2005). The results of this study indicate that the module is excellent and suitable for learning. Keywords: learning module, 唐诗 (Tangshi), literature Study, R&D